2015
DOI: 10.1186/s12889-015-1463-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing biomarkers and neuropsychological outcomes in rural populations exposed to organophosphate pesticides in Chile – study design and protocol

Abstract: BackgroundHealth effects of pesticides are easily diagnosed when acute poisonings occurs, nevertheless, consequences from chronic exposure can only be observed when neuropsychiatric, neurodegenerative or oncologic pathologies appear. Therefore, early monitoring of this type of exposure is especially relevant to avoid the consequences of pathologies previously described; especially concerning workers exposed to pesticides on the job. For acute organophosphate pesticides (OPP) exposure, two biomarkers have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…A study conducted in Chile (9) reports that human exposure to organophosphorus pesticides has been extensively documented, showing it is a health problem that is especially associated with rural workers in developing countries. Another study conducted in Kuwait reports that poisoning-caused suicide was the third most common modality of death and is an important problem in the developing world due to ample availability and easy access to substances by people susceptible to committing suicide (10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Chile (9) reports that human exposure to organophosphorus pesticides has been extensively documented, showing it is a health problem that is especially associated with rural workers in developing countries. Another study conducted in Kuwait reports that poisoning-caused suicide was the third most common modality of death and is an important problem in the developing world due to ample availability and easy access to substances by people susceptible to committing suicide (10) .…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, the signs and symptoms recurrent among adult male victims of acute carbamate poisoning and who composed the case group in this study, as identified on the reporting forms were: myosis, drooling, muscle twitching, sweating, vomiting, and bronchorrhea. It is worth noting that the literature describes acute poisoning as being relatively easy to diagnose because it is accompanied by cholinergic signs and symptoms (9) .…”
Section: Discussionmentioning
confidence: 99%
“…It could also be useful. For example, in the mentioned study about pesticide exposure in agricultural workers and cognitive impairment, gender turned out to be a confounder [7]. This resulted from the type of work performed differing between men and women.…”
Section: Cohort Studies In Health Sciencesmentioning
confidence: 99%
“…Selection criteria must be clearly defined from the beginning of the study in a way that ensures that biases are avoided. For example, a research was conducted with the objective of assessing the association between exposure to pesticides and neurocognitive impairment, including fine Limitations and Biases in Cohort Studies http://dx.doi.org/10.5772/intechopen.74324 motor coordination [7]. The researchers used Purdue Pegboard and MOART reaction time tests to measure the outcome.…”
Section: Selection Biasmentioning
confidence: 99%
“…To that end, sampling was performed before and during the spraying season. The detailed description of the study protocol can be obtained in a recent study from our group [ 16 ].…”
Section: Introductionmentioning
confidence: 99%